Khawaja Yusuf Hemedani: The Inspirer of Two Major Sufi Tariqas - Mansurov, Fatkhiddin; Faudzinaim, Badaruddin (Harran University, 2011)
The great Sufi scholar Khwaja Yusuf Hemedani who has played a major role in the formation of Sufi tariqas in Central Asia and Khorasan has not been comprehensively studied so far in terms of his life, activities and works. And the limited numbers of studies that have been undertaken so far were aimed towards elaborating his certain aspects. One of most significant contributions of Hemedani in the history of Sufism was that he had guided the founders of the Khwajagan-Naqshbandiyya and Yasawiyya tariqas that had been founded in Central Asia and have spread all around the world.